Experimental Investigation on Suffusion Characteristics of Cohesionless Soils Along Horizontal Seepage Flow Under Controlled Vertical Stress - Deng, Gang; Zhang, Liang-Liang; Chen, Rui; Liu, Lei-lei; Shu, Kai-Xiang; Zhou, Zhi-Le (Frontiers in Earth Science, 2020)
Suffusion is one of the main modes of internal erosion leading to selective erosion and gradual migration of fine soil particles through the voids of soil skeleton formed by coarse soil particles under seepage flow. Suffusion may induce deterioration and even failure of hydraulic geo-structures, such as embankment dams, dikes, levees, as well as landslide dams, if they are formed by gap-graded cohesionless soils. Soil mass in the hydraulic geo-structures is always subjected to overburden load and seepage through the soil mass generally has a large component along the horizontal direction. In the literature, however, little attention has been paid to the horizontal seepage-induced suffusion under controlled vertical stress. In this study, horizontal seepage-induced suffusion tests were carried out using a testing apparatus with controllable vertical stress and hydraulic gradient. The seepage flux and eroded fine particle mass, as well as local hydraulic gradients can be measured. The effects of initial dry density and initial fines content on suffusion characteristics of a cohesionless soil were investigated. Test results showed that after the initiation of suffusion, alternate decrease and increase in the coefficient of permeability occurred possibly due to alternate clogging and dredging of soil pores by the movable fine particles. Uneven distribution of local hydraulic gradients along the flow path was observed and this could be regarded as a sign of the initiation of suffusion. Both initiation and failure hydraulic gradients increased with initial dry density and initial fines content.